Critical requirements of integrated quality management system for project manager in construction - Sun, Zhendong (2015)
ISO 9001-based quality management systems (QMS) have been widely adopted in the global construction arena. Construction industry is a project-based industry where different parties work together. However, different parties work towards individual objective and separate the construction design, information, documents and data during the integrated works. These issues make cost and time overruns, more resources and materials are used and project can’t complete within the agreed budget, time and specifications. The objectives of this study are (1) to identify the requirements of integrated QMS for project manager in the construction project and (2) to determine the critical requirements of integrated QMS for project manager in the construction project. This study has taken a construction company named China Railway Group Limited (CREC). A total of 15 experts in China Railway Group Limited (CREC) were randomly selected to be the respondents of the study. Generally, the research design applied in this research consists of five stages which are preliminary stage, literature review, research methodology, data analysis and findings, as well as conclusion and recommendation. Ten requirements of project manager in construction had found out which were 1.Management Leadership, 2.Customer Relationship Management, 3.Resources Management, 4.Measurement and Feedback, 5.Systems and Process, 6.Continuous Improvement System, 7.Supplier Quality Management, 8.Improvement Techniques, 9.Education and Training, 10.Working Environment and Culture. Analytic hierarchy process (AHP) were used in this study. Pairwise Comparisons Matrix, Standardized Matrix and Consistency Test were used to analyze the data. For the result, the study finds that the critical requirements for project manager in integrated quality management system are Resource Management (14.67%), Continuous Improvement System(14%) and Management Leadership (13.4%).